Transhumanisme dan Pemahaman Kekristenan tentang Hak untuk Hidup dalam Wajah Rekayasa Genetika Manusia - Simanjuntak, Nadia Resiana; Marpaung, Frans Soma; Harianja, Mikael (Sekolah Tinggi Diakones HKBP, 2025)
This article discusses the perspective of transhumanism and the Christian view of human genetic engineering and the right to life. In this context, there is a gap in thinking between technology and theology. Transhumanism encourages the use of genetic engineering to improve the quality of human life. One of transhumanism's endeavours in the field of biotechnology is genetic engineering to create quality humans by directly manipulating or modifying the genetic material (DNA) of an organism. Meanwhile, Christianity emphasises that creation and the right to life are gifts from God that must be guarded and respected. This research uses a literature study method to explore the origin of humans, the use of genetic engineering, its social impact, and the church's attitude towards transhumanism. The findings show that the use of genetic engineering on humans gives rise to a conflict between human intervention and the will of God, as well as the potential for complex social impacts. Especially when confronted with human identity as a creation, not a creator. The church's response varies but reflects an attempt to mediate the gap between technology and religious belief, often with an emphasis on ethical principles. However, this study will delve deeper into the theory of creation aimed at answering the question of human intervention in God's creation as creator through human genetic engineering. Strengthening this research, therefore, is the need for an in-depth and perspective dialogue between science, religion, and society.